2021
DOI: 10.3390/molecules26216559
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Available Flavonoid Aglycones as Potential Antiviral Drug Candidates against SARS-CoV-2

Abstract: Flavonoids are important secondary plant metabolites that have been studied for a long time for their therapeutic potential in inflammatory diseases because of their cytokine-modulatory effects. Five flavonoid aglycones were isolated and identified from the hydrolyzed aqueous methanol extracts of Anastatica hierochuntica L., Citrus reticulata Blanco, and Kickxia aegyptiaca (L.) Nabelek. They were identified as taxifolin (1), pectolinarigenin (2), tangeretin (3), gardenin B (4), and hispidulin (5). These struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 68 publications
1
49
0
Order By: Relevance
“…Several herbal medicines have been assessed for their anti-SARS-CoV-2 activity either as crude extracts or as purified plant-origin components. Several herbal extracts and components could hinder SARS-CoV-2 replication in vitro and relieve COVID-19 symptoms in vivo in experimental and clinical settings such as Echinacea purpurea extract, Cuphea Ignea extract, Pomegranate Peel extract and juice (Punica Granatum), Clove (Syzygium aromaticum L.), and bioactive polyphenolic compounds, namely curcumin, quercetin, and hesperidin [2,45,[247][248][249][250][251][252][253]. However, the main limitation of the herbal medicines is still the inconsistency of the antiviral efficacy between the cell-based in vitro assays and in vivo experimental settings due to the high hydrophilicity and low oral bioavailability of the herbal medicine components [254].…”
Section: Herbal Therapymentioning
confidence: 99%
“…Several herbal medicines have been assessed for their anti-SARS-CoV-2 activity either as crude extracts or as purified plant-origin components. Several herbal extracts and components could hinder SARS-CoV-2 replication in vitro and relieve COVID-19 symptoms in vivo in experimental and clinical settings such as Echinacea purpurea extract, Cuphea Ignea extract, Pomegranate Peel extract and juice (Punica Granatum), Clove (Syzygium aromaticum L.), and bioactive polyphenolic compounds, namely curcumin, quercetin, and hesperidin [2,45,[247][248][249][250][251][252][253]. However, the main limitation of the herbal medicines is still the inconsistency of the antiviral efficacy between the cell-based in vitro assays and in vivo experimental settings due to the high hydrophilicity and low oral bioavailability of the herbal medicine components [254].…”
Section: Herbal Therapymentioning
confidence: 99%
“…Kickxia species, including K. aegyptiaca, were documented as significant traditional plants in the treatment of vascular diseases, haemorrhoids, and wounds, along with their uses as laxatives, anti-diabetics, anti-scorbutics, diuretics, and, tonics agents [ 12 , 14 ]. The phytochemical characterization of this plant revealed that it is rich in flavonoids, phenolic acids, glycosides, and iridoids [ 7 , 15 , 16 ]. The different K. aegyptiaca extracts and their isolated metabolites were documented to have antioxidant activity [ 17 , 18 ], larvicidal activity [ 18 ], and cytotoxic activity [ 15 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The different K. aegyptiaca extracts and their isolated metabolites were documented to have antioxidant activity [ 17 , 18 ], larvicidal activity [ 18 ], and cytotoxic activity [ 15 , 19 ]. Flavonoids, pectolinarigenin, tangeretin, and gardenin were also isolated from K. aegyptiaca, which exhibited potential antiviral activity against SARS-CoV-2 [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids, the most common group of polyphenolic compounds in the human diet, are found ubiquitously in fruits and vegetables, and studies support their potential use to treat various human diseases [ 40 , 41 ]. Additionally, flavonoids are considered to have notable beneficial health effects, including antibacterial, anti-inflammatory, antioxidant, and a wide range of antiviral activities against several human viruses [ 15 , 39 , 41 , 42 ]. Hence, flavonoids are key components of various dietary supplements for the relief of medical conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these considerations, we combined here non-toxic dietary supplements composed of zinc picolinate, copper sulfate, and the flavonoids Epigallocatechin-3-gallate (EGCG), Quercetin, Taxifolin (dihydroquercetin), and Naringenin, that act as zinc ionophores and transport zinc cations through the cell membrane [ 26 , 40 , 42 , 43 , 44 , 45 , 46 , 47 ]. The combination effectively inhibited in vitro viral replication in several cell types, including human lung cells.…”
Section: Introductionmentioning
confidence: 99%